PET/CT Integrated With CT Colonography in Preoperative Obstructive Colorectal Cancer by Incomplete Optical Colonoscopy: A Prospective Study. (December 2020) - Sánchez-Izquierdo, Nuria; Pagès, Mario; Mayoral, Maria; Rubello, Domenico; Colletti, Patrick M.; Campos, Francisco; Romero, Inmaculada; Casanueva, Sebastián; Fritsch, Andrea; Fuster, David
Abstract : Aim: The aim of this study was to evaluate if integrating whole-body PET/CT with CT colonography (PET/CTC) improves the preoperative diagnosis of obstructive colorectal cancer (CRC). Methods: We prospectively included 47 consecutive patients (18 women and 29 men; mean age, 71 ± 14 years) suspected of having CRC by optical colonoscopy, which was not completed due to obstructive masses. To perform PET/CTC, a small caliber Foley catheter was inserted to distend the colon with CO2 insufflations. Polyps measuring 10 mm or larger were considered as high risk of malignancy. All findings were histologically confirmed. Results: Colorectal cancer was localized in the sigmoid (n = 21), rectum (n = 7), rectosigmoid junction (n = 5), ascending (n = 7), descending (n = 5), and transverse (n = 2) colon. All tumors showed FDG uptake (mean ± SD SUVmax, 20.02 ± 9.9) including one synchronic tumor (SUVmax, 10.46). Forty-seven polyps were histologically confirmed as smaller than 10 mm (n = 35) and 10 mm or larger (n = 12). All 12 polyps 10 mm or larger showed FDG uptake (SUVmax range, 3.08–19.5), but only one smaller than 10 mm could be identified by PET. Pathological lymph nodes were diagnosed in 17/47 cases after surgical removal with a sensitivity and specificity for CTC and PET/CTC of 71% and 97% and 59% and 100%, respectively. Liver metastases were confirmed in 9 patients and in 4/9 along with lung metastases (n = 2) or implants (n = 2), showing a sensitivity and specificity for CTC of 89% and 100% and both 100% for PET/CTC. Conclusions: PET/CTC is a reliable technique for staging CRC and diagnosing synchronous tumors. In this series, PET/CTC was not able to identify small polyps but showed potential use for ruling out 10 mm or larger polyps at high risk of malignancy.